Atypical compaction behaviour of disordered lactose explained by a shift in type of compact fracture pattern - Samaneh Pazesh; Ann-Sofie Persson; Göran Alderborn (Elsevier, 2019)
The objective was to investigate tabletability and compactibility for compacts of a series of α-lactose monohydrate powders with different degree of disorder. Regarding the tabletability, the powders of high degree of disorder displayed similar behaviour that deviated markedly from the behaviour of the crystalline powders and the milled powder of modest degree of disorder. The Ryshkewitch-Duckworth equation, describing compactibility, was nearly linear for the crystalline powders, while for the disordered powders the model failed to describe the relationships, i.e. the disordered powders were characterised by a plateau in the Ryshkewitch-Duckworth plots over a relatively wide range of compact porosities. It was concluded that the difference in compaction behaviour of the milled particles compared to the crystalline powders was primarily explained by the increased particle plasticity of the disordered particles. The plateau in the Ryshkewitch-Duckworth plots obtained for the disordered powders was explained by a change in the fracture behaviour of the compacts, from an around grain to an across grain fracture pattern. This implied that the disordered particles can be described as a type of core-shell particles with an amorphous shell and a defective crystalline core. Keywords: Lactose, Tensile strength, Compaction pressure, Porosity, Core-shell particles, Tablet fracture